2003
DOI: 10.1088/0268-1242/19/1/004
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical comparison of the pressure dependence of the threshold current of phosphorus-, aluminium- and nitrogen-based 1.3 µm lasers

Abstract: A comparative study of the three competing laser materials, InGaAsP-InP, AlGaInAs-InP and InGaAsN-GaAs, has been undertaken, for the first time, involving threshold characteristics with pressure. In our theoretical study we investigate the factors that influence the material gain performance, the threshold characteristics and the pressure dependence of each of the laser systems. We find that AlGaInAs and InGaAsN active layer materials have substantially better material gain performance than the commonly used I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…For the band structures of laser systems, the material parameters except for the band gap energies are linearly interpolated from those of binary materials [28,29]. We calculate the bulk band gap energy of GaInNAs by means of band-anti-crossing model [18] and the details of the calculations can be found in our recent paper [30].…”
mentioning
confidence: 99%
“…For the band structures of laser systems, the material parameters except for the band gap energies are linearly interpolated from those of binary materials [28,29]. We calculate the bulk band gap energy of GaInNAs by means of band-anti-crossing model [18] and the details of the calculations can be found in our recent paper [30].…”
mentioning
confidence: 99%
“…We have taken constant carrier concentration as 1.5 × 10 18 cm −3 . The threshold current density is found to enhance with the application of hydrostatic pressure for all the values of dot radii . It is also observed that the threshold current density is increased when the pressure effect is included.…”
Section: Resultsmentioning
confidence: 68%
“…The simple scheme described above allows the calculation of the maximum gain as a function of carrier density in the well [3,7], and thus its dependence on the temperature and hydrostatic pressure. Assuming that the dominant carrier recombination process is the radiative recombination (i.e., neglecting nonradiative recombination paths such as the Auger recombination), the radiative part of the threshold current density can be written as [3,7] …”
Section: Simple Modelmentioning
confidence: 99%